THE PROBLEM IN LEARNING READING FACED BY THE STUDENT AT THE FIRST YEAR OF SMK HARAPAN KARTASURA - A'isyah, Siti (2010)
This research aims at describing the problems in learning reading faced by the students at the first year of SMK Harapan Kartasura and the alternative solutions done for solving the students' problems in learning reading. This research was done 10 until15 May 2010. From this research is a descriptive qualitative study in which the data are taken from interview, events, informants, and documents. The techniques of collecting data are interview, questionnaire, observation and test of learning reading faced by the students and alternative solutions done for solving the students' problems in learning reading. The result of the research shows that the problems in learning reading faced by the students at the first year of SMK Harapan Kartasura are vocabulary, meaning, main idea, and pronounciation. There are some alternative solutions done for solving the students' problems in learning reading, namely; for vocabulary the teacher gave the vocabulary which is difficult for the students first and gave the meaning of each difficult vocabulary. For meaning the teacher asked the students to open the dictionary first and if the students still do not understand, the teacher gave explanation about the content. For main idea, the teacher gave explanation what the main idea is and gave an example of the main idea in the text. For pronounciation the teacher gave the motivation to practice students' English in students' daily life and the teacher pronunced the difficult words first, and then was followed by all the students together.